Implikatur Percakapan Bahasa Arab antar Tokoh dalam Film Arab Maklum: Kajian Pragmatis - Heni Wahyuni; Setiyawan, Agung (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
One linguistic phenomenon, namely conversational implicature, is not only found in everyday conversations, but this phenomenon is also often found in film dialogues. One of them is the Arabic Comedy Film Series Maklum. This research aims to elaborate on the implied meaning of the dialogues in the film using conversational implicature theory. This theory explains the implied meaning in an utterance which looks different from the sentence spoken by the speaker in a conversation. The implications in a conversation are determined by factors outside of language that involve the context of the speech and also the response of the interlocutor. This research is descriptive qualitative research. The data in the research was obtained using the listening method and note-taking techniques. The data that has been obtained is then analyzed using three content analysis techniques. The results of this research show that the comedy drama series entitled Arab Maklum is a series where the actors have dialogue using Indonesian and Aba Mahmud's family occasionally uses Arabic and there are several Arabic terms that are rarely used or are even foreign to the ears of the listeners. One of the expressions used in this series that is unfamiliar to listeners is Sengke, which has the meaning you want.